Volunteering, religiosity and well-being: interrelationships among Australian churchgoers - Mollidor, Claudia (Mental health, religion & culture, 2015)
Existing research has mostly found positive, but sometimes inconclusive and contradictory, results about the relationships between volunteering and well-being, as well as between church attendance and volunteering. This paper aims to clarify how volunteering and religious beliefs and practices are related to well-being among Christian churchgoers. Utilising data from the 2011 Australian National Church Life Survey, volunteering was found to partially mediate the positive relationship between religiosity and well-being (life satisfaction), but only for some denominational groupings. Part of the reason why church attenders with high religiosity have higher well-being is because they are more likely to volunteer. The implications of these findings are discussed within the context of economic, managerial, public health and religious parameters.